1990
DOI: 10.1002/pd.1970100406
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester maternal serum biochemical indicators in Down syndrome

Abstract: A set of 21 early maternal serum samples (19 first-trimester and two at 14 weeks) from pregnancies resulting in a child with Down syndrome was matched for gestation and length of storage with 63 samples from unaffected pregnancies. The concentrations of alpha-fetoprotein (AFP), unconjugated oestriol (uE3), human chorionic gonadotrophin (hCG), pregnancy-specific beta 1-glycoprotein (SP1), and placental alkaline phosphatase (PALP) were measured. The ratios of the medians for Down syndrome pregnancies compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1

Year Published

1994
1994
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 18 publications
(11 reference statements)
5
40
1
Order By: Relevance
“…First-trimester screening with MS-AFP levels has been evaluated by some authors (Brambati et al, 1986;Milunsky et al, 1988;Cuckle and Wald, 1988;Brock et al, 1990;Crandall et al, 199 1, 1993;Berry et al, 1995;Powell and Grudzinskas, 1996), suggesting that measurement of this analyte is less discriminatory for DS than in the second trimester (Van Lith, 1994). Our results are in agreement with these reports, with a mean of MOM in DS cases of 0.90.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…First-trimester screening with MS-AFP levels has been evaluated by some authors (Brambati et al, 1986;Milunsky et al, 1988;Cuckle and Wald, 1988;Brock et al, 1990;Crandall et al, 199 1, 1993;Berry et al, 1995;Powell and Grudzinskas, 1996), suggesting that measurement of this analyte is less discriminatory for DS than in the second trimester (Van Lith, 1994). Our results are in agreement with these reports, with a mean of MOM in DS cases of 0.90.…”
Section: Discussionsupporting
confidence: 95%
“…Previous reports have shown that an increase of hCG in DS pregnancies is observed from 14 weeks' gestation but not earlier (Cuckle and Wald, 1988;Brock et al, 1990;Van Lith, 1992 1993; Macintosh et al, 1994). One reason may be that since our DS cases were diagnosed by firsttrimester CVS, some of the pregnacies may have been predetermined to miscarry and for this reason lower values of p-hCG do not necessarily reflect the chromosomal anomalies (Macintosh et al, 1994).…”
Section: Discussioncontrasting
confidence: 56%
“…We have already demonstrated elevated serum levels of immunoreactive PLAP in patients with malignant pelvic disease (Ind et al, 1993a). Furthermore, aberrant levels of PLAP have been shown to be associated with Down's syndrome pregnancies when measured by this IRMA but not by the IAEA (Brock et al, 1990;Ind et al, 1993b). Similarly, we have demonstrated an association between PLAP levels and blood groups which had not previously been recognised (Ind et al, 1993c).…”
Section: Discussionsupporting
confidence: 56%
“…However the detection rate of the test is only about 60% [12], and there is no agreement on the contribution of unconju gated estriol to a better performance [13,14]. Furthermore, the need for an earlier identifi cation of patients at risk urges the search for new markers which can be used during the first trimester [15][16][17][18][19],…”
Section: Discussionmentioning
confidence: 99%